(untitled) (Ibrahim Cardiac Medical Journal, 2012)
Coarctation of aorta (CoA) is a congenital vascular malformation usually diagnosed and corrected early in life but the diagnosis is missed or delayed unless there is a high index of suspicion. Long-term survival is exceptional in patients with untreated aortic coarctation. In our case report, we present a late diagnosis of aortic coarctation in a 24-year-old male who was relatively asymptomatic until he presented with progressive exertional dyspnoea, fatigue, headache and poorly controlled hypertension despite getting a combination of antihypertensive agents in his 2nd decade of life. The patient was managed by surgery of aorta. The coarcted segment was mobilized, resected totally followed by insertion of interposition tube graft of prosthetic material (PTFE) 20 mm in diameter with ligation and transfixation of patent ductus arteriosus (PDA). After 4-year follow-up visit, the patient is in good clinical condition. Ibrahim Cardiac Med J 2012; 2(2): 50-53